Arando a terra, registrando a vida: os sentidos da escrita de diários na vida de dois agricultores - Thies, Vania Grim (2008)
This work has as objective to analyze the directions of the culture written in the daily life of two farmers with little schooling, inhabitants of the agricultural zone of the cities of Pelotas and Morro Redondo (Rio Grande do Sul, BR). It is about to understand and to analyze the usual writing of dailies of two brothers: Aldo Schmidt (60 years) and Clemer Schmidt (56 years). Aldo used to write while still living in the paternal house, from 1972 to 1974, in his period of bachelor. In 1976, Aldo was married, constituted his family and continued writing dailies with the "new" family, as still makes currently. On the other hand, his brother Clemer started to write dailies in 1975, while single one, in the father s house, up to 1979, when he married and stopped to write. The methodology used is the analysis of the notebooks of dailies registers, together with oral history from half-structuralized interviews. The registers in the dailies are related to the organization of the work in the daily of the rural zone, as well as other aspects related to the climate, leisure and other social events of the farmer s life. The research shows that the motivation for the writings is the work in the farming, although the content of the notebooks tells about the private and also public life of the family, demonstrating that the registers exceed the sphere of the work and reach other directions.